The MeerKAT Radio Frequency Interference Environment - Sihlangu, Isaac (Department of Astronomy, 2020)
Radio signals from astronomical sources are extremely weak and easily distorted/- corrupted or overwhelmed by man-made radio signals such as cellphones, satellites, aircraft and telescope electronics. These Radio Frequency Interference (RFI) are increasingly threatening radio observatories due to our increasingly technological world. To detect and mitigate RFI, observatories need to understand their RFI environment, what contributes to it and how it is changing. While there are few dedicated RFI monitoring systems on the MeerKAT site, the most sensitive RFI detector is the MeerKAT array itself. In this thesis we use approximately 1500 hours of MeerKAT observations to create a multi-dimensional view of the RFI at the MeerKAT site. Here we investigate a probabilistic approach to characterise the RFI environment around the MeerKAT radio telescope. In order to achieve our goal, we propose the MeerKAT Historical Probability of RFI (KATHPRFI) framework. We produced the high level requirements of the KATHPRFI framework driven by the needs of the MeerKAT users. The design approach and the design decision of the framework is presented that cover both the software and hardware constraints. The KATHPRFI produces a 5-dimensional array of the RFI probability as measured by the MeerKAT telescope during the commissioning phase (May 2018 - December 2018) for each observation file. From the 5-D array, we extracted various statistics and characterised the RFI environment around MeerKAT site. We found that there is a correlation between RFI occupancy and the time of the day which is most probably related to human activities. Furthermore, we found a correlation between the time of the day and flights passing over a region of site. Our results showed that the highest probability of RFI points towards a region including nearby towns. The results obtained are consistent with the argument that the major RFI sources for MeerKAT site are the Global Positioning System (GPS) satellite, flight Distance Measurement Equipment (DME) and the Global System for Mobile Communications (GSM). Our data also showed that the RFI occupancy decreases with an increase of baseline length, this is a result of moving RFI sources with respect to the static sky. Therefore, the phase of the RFI changes rapidly on long baselines compared to short baselines. As a result when a correlation is carried out the RFI amplitude will vanish less on short baselines compared to the long baselines. Our results provide the first highly detailed view of the MeerKAT RFI environment allowing us to track the historical evolution of the RFI, both on average, and as a function of frequency, baseline and direction. With historical baselines known, one can also provide alerts about sudden changes. This could be due to new sources of RFI or stem from any outliers in the data, which could signal telescope or correlator issues. Hence the KATHPRFI framework also provides a window into the operational health of the telescope.